Transkrypcja czy transliteracja tekstów muzułmanów litewsko-polskich pisanych alfabetem arabskim? (Wprowadzenie do dyskusji) - Łapicz, Czesław (Slavistica Vilnensis, 2009)
If Kitab studies are to become an independent sub-discipline of language study, they should develop their own research methods. One of the basic conditions for the development of integrated research into Kitab studies is to work out a universal transliteration and transcription system that would be accepted and used by all (or by the majority of) researchers converting Tartar texts written in the Arabic alphabet into Latin and Cyrillic alphabets. Given the fact that such a system cannot be developed by one researcher alone, the article postulates that an international team of researchers and experts be formed to work out a universal system of transcription and transliteration of the manuscripts of Muslims in the Grand Duchy of Lithuania. In order to justify this idea, the author provides examples of the misinterpretation of language facts arising from adopting a subjective, individual, and accidental alphabet conversion system.